Efficient Synthesis of Intrinsically Conducting Polypyrrole Nanoparticles Containing Hydroxy Sulfoaniline as Key Self-Stabilized Units - Li, X; Hou, Z; Huang, M; Moloney, M (2009)
Self-stabilized copolymer nanoparticles are easily and productively synthesized by a chemical oxidative polymerization of pyrrole (Py) and 2-hydroxy-5-sulfonic aniline (HS) in 1 M HCl without any external template. UV-vis, IR, 1D 1H NMR, 2D 1H-1H COSY NMR, and 2D 1H-13C HSQC NMR all indicate that a real copolymerization occurs between HS and Py comonomers and Py units construct the main position of the copolymer. On the basis of the elemental analysis, the reactivity ratios of HS and Py comonomers are calculated to be 0.043 and 1.14, respectively. The polymerization yield, size, morphology, and electrical conductivity of the copolymer particles can significantly be optimized by the comonomer ratio, polymerization temperature, and ammonium persulfate oxidant/comonomer ratio. The copolymer particles always keep narrow size distribution with a small polydispersity index (PDI) of 1.05-1.08. HS/Py(50/50) copolymer nanoparticles synthesized at 0 °C are found to generally have irregular granular morphology with the smallest diameter of 35-60 nm and the lowest PDI of 1.05 by laser particle-size analyzer, FE-SEM, and TEM. The mechanisms of the formation and intrinsic self-stabilization of the nanoparticles are proposed based on the powerful static repulsion from negatively charged sulfonic and hydroxyl groups on the nanoparticles. Through simple dedoping and redoping procedures, the copolymer particles exhibit a widely adjustable conductivity from 10-9 to 1.12 S cm-1. These copolymer nanoparticles show high conductivity, good self-stability, and powerful redispersibility in water and organic media. Nanocomposite films of the copolymer nanoparticles in polyvinylalcohol possess a low percolation threshold down to 0.09 wt % as well as retain 80-95% transparency and 10 2-108 times the conductivity of the pure polyvinylalcohol film in the nanoparticle loading from 0.09 to 3 wt %. © 2009 American Chemical Society.